Strategy Management for Sustainability: ESG Implementation in Modern Business - Davinnizam R. Diandria; Harry Z. Soeratin; Munasiron Miftah (International Journal of Environmental, Sustainability and Social Science, 2026)
This research aims to understand how ESG (Environmental, Social, and Governance) implementation strategies can be optimized to improve the company's financial performance and long-term value. In addition, this research identifies the main obstacles that companies face in adopting and integrating ESG principles into their business strategies, especially in the current context of globalization and market complexity. This research also analyzes the influence of ESG implementation on a company's reputation and image in the eyes of stakeholders, including investors, consumers and the wider community. The research results show that effective ESG implementation can reduce operational risks, increase efficiency, and attract sustainable investment, ultimately strengthening a company's competitiveness. However, challenges such as measurement difficulties, implementation costs, and pressure from stakeholders remain obstacles that need to be overcome. Overall, successful ESG integration can create long-term, sustainable value for a company and all its stakeholders.